Scintigraphy in lumbosacral and sacroiliac region pathologies in horses - Cerqueira, Francisco Aníbal Pedrosa (2024)
The lumbosacral joint in horses is the most mobile intervertebral joint between the thoracic and pelvic regions, making it more susceptible to injury than other intervertebral joints. On the other hand, sacroiliac joint disease has been classified as one of the main causes of diminished athletic capacity in sport horses. However, due to the close proximity of these two joints, there is a high biomechanical relationship, which can mean that injury in one joint can cause changes in the other. Injuries to these joints have sparked a great deal of diagnostic interest due to the loss of athletic capacity that horses can show. The difficulty of detecting lameness in the pelvic limbs, the presence of other pathologies and the ease of observing lesions in the rest of the horse's appendicular system mean that some degree of chronicity is observed when diagnosing lesions in the lumbosacral and sacroiliac joints. This leads to less efficient treatment and a less favourable prognosis. The purpose of this study was to analyse the value of scintigraphy as a diagnostic method for lesions in the sacroiliac and lumbosacral regions and to verify its association with clinical data or lesions in other regions. The data was collected from horses admitted at Liphook Equine Hospital between 2016 and 2023, in a sample of 55 horses with a history of hindlimb lameness with loss of performance and radiopharmaceutical uptake in the sacroiliac joint. Scintigraphic images with radiopharmaceutical uptake were also evaluated in the forelimbs, cervical, thoracic and lumbar vertebrae, lumbosacral region and pelvic limbs. Data was also collected on the reaction the flexion, extension and latero-flexion tests (Provocation tests). From this population, 26 animals showed uptake in the lumbosacral region (between both sacral tuberosities). Although no association was observed between radiopharmaceutical uptake in the lumbosacral region and the other clinical data, nor between the reaction to provocation tests and the other variables, it was possible to see that the uptake in LS region and the presence of a positive reaction to the provocation tests should redirect us to perform a transrectal ultrasound, and that the presence of a positive reaction to the provocation tests is associated with presence of uptake in the hindlimbs together with presenting only hindlimb lameness. This is the first study in which both the sacroiliac and lumbosacral joints are considered in the scintigraphic images of animals with hindlimb lameness. The importance of observing the radiopharmaceutical uptake between both sacral tuberosities and performing the transrectal ultrasound scan in conjunction with the other diagnostic tests allows for a more precise diagnosis and more targeted treatment.